Gustav Bychowski papers - Bychowski, Gustav, 1895-1972.
Letters addressed to Bychowski and his wife Maria from colleagues, students, and analysands; programs; and photographs. Correspondents include Heinz Hartmann and Alexander Mitscherlich.
In part, photocopies.
Psychoanalyst.
Collection material in English, German, French, and Italian.
Forms part of: Sigmund Freud collection.
Keywords: Bychowski, Maria -- Correspondence; Hartmann, Heinz, -- 1894-1970 -- Correspondence; Mitscherlich, Alexander, -- 1908-1982 -- Correspondence; Psychoanalysis; Psychoanalysts